The Routledge handbook to the political economy and governance of the Americas
1 online resource
Keywords: "This handbook explores the political economy and governance of the Americas, placing particular emphasis on collective and intertwined experiences. Forty-six chapters cover a range of inter-American key concepts and dynamics"--